Developing A Combination of Health Exercises for Middle-Aged Men Aged 45-60 (Eurasian Scientific Herald, 2022)
This article discusses the development of a set of health exercises for middle-aged men, especially 45-60 ages. It describes the exercises that can be performed on a daily basis, as well as complex actions that need to be done separately.